Taxonomic status of Veithia Oudemans, 1941 and redescriptions of two species described by Oudemans (Acari: Smarididae) - Zhang, Zhi-Qiang (Zootaxa, 2003)
Veithia Oudemans, 1941, previously considered nomen dubium, is revisited and confirmed a junior synonym of Fessonia Heyden, 1826. Fessonia schneideri (Oudemans, 1941) comb. nov. and Fessonia assmuthi (Oudemans, 1941) comb. nov. are redescribed from type specimens and compared with related species.